Chapter Bruno Trentin e l'Europa in prospettiva transnazionale - Del Rossi, Maria Paola (Studi e saggi, 2023)
Starting from the reconstruction of Bruno Trentin's transnational network of political and intellectual relationships, the essay analyzes the European and international dimensions of his political and trade union activity from the years of his leadership of the General Secretary up to his experience in the European Parliament. The union of rights and the political program on Europe are the main themes of the essay. They are combined with the question of the construction of political Europe and the institutional reform of the Union, and culminate in his contribution to the European Parliament, in the aftermath of the elaboration of the "European Charter of Fundamental Rights of the European Union," and on the occasion of the debate on the European Constitution.